BioChaperone Lispro versus faster aspart and insulin aspart in patients with type 1 diabetes using continuous subcutaneous insulin infusion: A randomized euglycemic clamp study. Issue 4 (17th January 2019) - Heise, Tim; Meiffren, Grégory; Alluis, Bertrand; Seroussi, Cyril; Ranson, Aymeric; Arrubla, Jorge; Correia, José; Gaudier, Martin; Soula, Olivier; Soula, Rémi; DeVries, J. Hans; Klein, Oliver; et al.
Abstract : We investigated the pharmacodynamics (PD) and pharmacokinetics (PK) of BioChaperone insulin Lispro (BCLIS), faster insulin aspart (FIA) and insulin aspart (ASP) in patients with type 1 diabetes using an insulin pump. In this randomized, double‐blind, three‐way crossover glucose clamp study, 43 patients received a bolus dose of each insulin (0.15 U/kg) in addition to a basal rate (0.01 U/kg/h), delivered via an insulin pump. With BCLIS, the AUC‐GIR, 0–60 minutes (primary endpoint) was improved compared to ASP (least square means ratio, 1.63; 95% CI, 1.44–1.88; P < 0.0001) and was similar compared to FIA (least square means ratio, 1.06; 95% CI, 0.94–1.18; P = 0.4609). BCLIS showed faster‐on PD (tearly0.5GIRmax ) than ASP and faster‐off PD (tlate0.5GIRmax ) than both FIA and ASP. BCLIS also demonstrated significantly higher early exposure (AUCins, 0–60 minutes) and lower late exposure (AUCins, 120–600 minutes) than both other insulins. In patients with type 1 diabetes using an insulin pump, BCLIS better mimics prandial insulin secretion and action than ASP and shows a faster off‐PD than FIA.